Plasma growth differentiation factor 15 is associated with weight loss and mortality in cancer patients. Issue 4 (30th April 2015) - Lerner, Lorena; Hayes, Teresa G.; Tao, Nianjun; Krieger, Brian; Feng, Bin; Wu, Zhenhua; Nicoletti, Richard; Chiu, M. Isabel; Gyuris, Jeno; Garcia, Jose M.
Abstract: Background: Cancer‐related weight loss is associated with increased inflammation and decreased survival. The novel inflammatory mediator growth differentiation factor (GDF)15 is associated with poor prognosis in cancer but its role in cancer‐related weight loss (C‐WL) remains unclear. Our objective was to measure GDF15 in plasma samples of cancer subjects and controls and establish its association with other inflammatory markers and clinical outcomes. Methods: We measured body weight, appetite, plasma GDF15, and other inflammatory markers in men with cancer‐related weight loss (C‐WL, n = 58), weight stable patients with cancer (C‐WS, n = 72), and non‐cancer controls (Co, n = 59) matched by age and pre‐illness body mass index. In a subset of patients we also measured handgrip strength, appendicular lean body mass (aLBM), Eastern Cooperative Oncology Group (ECOG), and Karnofsky performance scores. Results: GDF15, interleukin (IL)‐6 and IL‐8 were increased in C‐WL versus other groups. IL‐1 receptor antagonist, IL‐4, interferon–gamma, tumour necrosis factor alpha, and vascular endothelial growth factor A were increased in C‐WL versus C‐WS, and Activin A was significantly downregulated in Co versus other groups. C‐WL patients had lower handgrip strength, aLBM, and fat mass, and Eastern Cooperative Oncology Group and Karnofsky performance scores were lower in both cancer groups. GDF15, IL‐6, and IL‐8 significantly correlated with weight loss; GDF15 negatively correlated with aLBM, handgrip strength, and fat mass. IL‐8 and Activin A negatively correlated with aLBM and fat mass. GDF15 and IL‐8 predicted survival adjusting for stage and weight change (Cox regression P < 0.001 for both). Conclusion: GDF15 and other inflammatory markers are associated with weight loss, decreased aLBM and strength, and poor survival in patients with cancer. GDF15 may serve as a prognostic indicator in cancer patients and is being evaluated as a potential therapeutic target for cancer‐related weight loss.